IMPLEMENTATION OF CHILD-FRIENDLY SHOWS THROUGH SCHOOL TV CHANNELS - Lilis Amperawati; Rustatik Rustatik; Nanik Rahayu; Sri Watini (Jurnal Scientia, 2022)
Early childhood education according to its goals must be able to cultivate character, talent, and mental and physical conditions and teach them about understanding, peace, gender equality, and friendship between people while respecting their own culture and that of others. In line with this, of course, schools must ensure that children's rights to develop their interests, character, and self-confidence can be accommodated through activities carried out at school. To facilitate this problem, the existence of a School TV channel program can be the solution. Writing this article aims to find out the implementation in providing children-friendly shows through the School TV channel. The method used is a qualitative method with observation techniques and data collection in the form of information about the benefits of school TV channels for students, teachers, and parents. The results obtained show that the existence of School TV provides many benefits, especially for students in growing self-confidence, developing creativity, and limiting children's access to inappropriate information due to the development of an unrestricted flow of information. The right of children to get appropriate/child-friendly broadcasts will be fulfilled with information and educational services that are safe and follow their needs and age development because they are facilitated by their schools.